Epidemiological profile of postoperative digestive fistulas - Marochi, Bianca; Pereira, Daniela Thaís Lorenzi; Lattmann, Luiza Manfroi; Mais, Sthefany; Matos, Arthur Nathan Luiz Ferreira; Fukuchi, Thais Mayumi Komatsu; Beck Neto, Theodoro Busso; Chibata, Maurício; Almeida, Francisco Emanuel de (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Background and objectives: Gastrointestinal fistulas are anomalous communications between the digestive system and other structures. This article presents the epidemiological profile of patients who developed postoperative abdominal fistulas and their outcomes. Methods: Cross-sectional study that evaluated surgical procedures done in a 25 week period that presented risks for fistulous formations. Were analyzed age, type of the surgery (elective or urgent), pre-existing risk factors, need for post-surgical intensive care unit, type of fistula, reoperations to the fistula treatment, and outcome (discharge or death). Results: There were 1785 abdominal surgical procedures, with a fistula incidence of 1.8%. Most of the patients who developed fistulas were over 60 years old (71.4%), and surgeries that resulted in fistulous complications were mainly urgent (75.0%), with the need for intensive care in 46.9%. The most frequent types of fistula were enteral (52.3%) and biliary (23.8%), and surgical treatment took place in 53.1% of cases. Late hospital discharge was predominant in these patients (40.6%), and the death rate was 3.1%. Discussion: These complications are common after abdominal surgery and require clinical attention. There is a correlation between the formation of the fistulas and urgent surgery procedures, directly impacting the length of hospital stay. Conclusion: The risk factors of fistula development are advanced age and the presence of malignant disease. They are more prevalent in urgent surgeries and patients were more likely to need reoperation and have a delay on discharge.